2021
DOI: 10.2340/00015555-3922
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Affective Symptoms and Quality of Life in Patients with Atopic Dermatitis

Abstract: The aim of this study was to detect demographic and clinical factors associated with affective symptoms and quality of life in patients with severe atopic dermatitis. First, one-way analyses of variance and correlations were performed to compare a large set of qualitative and quantitative clinical variables. Three final multivariable regression models were performed, with depression/anxiety subscales and Dermatology Life Quality Index scores as dependent variables, and the factors that were statistically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…Scoring from each item ranges from 0 to 3, thus the total score for each subscale can range from 0 to 21. A score > 7 in each subscale denotes the presence of clinically significant anxiety and depression 53 . The questionnaire was validated in Italian 54 .…”
Section: Methodsmentioning
confidence: 99%
“…Scoring from each item ranges from 0 to 3, thus the total score for each subscale can range from 0 to 21. A score > 7 in each subscale denotes the presence of clinically significant anxiety and depression 53 . The questionnaire was validated in Italian 54 .…”
Section: Methodsmentioning
confidence: 99%
“… 31 A recent study reported that previous treatment with systemic immunosuppressants, more severe depressive symptoms, itch, impaired sleep, and perceived severity of dermatological symptoms were significant predictors of poor quality of life. 32 Patients with AD have been found to exhibit inferior social functioning and mental health scores compared with the general population. Greater disease severity is associated with poorer quality of life and health-related quality of life, especially in children.…”
Section: Discussionmentioning
confidence: 99%
“…Over 80% of patients in dermatology clinics with AD and psoriasis suffer from chronic itch (19,20). About half of patients in dermatological clinics with AD have a high level of depressive disorders, which is more than 3.5 times higher than in the general population (5,21,22). The level of anxiety in adult patients with AD is positively correlated with the intensity of itch (23).…”
Section: Association Of Dermatological Itch Stress and Mental Disordersmentioning
confidence: 99%